2015
DOI: 10.5604/15093492.1173379
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of bone tissue around the distal part of Zweymüller stem

Abstract: Kli ni ka Or to pe dii Ogól nej, On ko lo gicz nej i Trau ma to lo gii, Uni wer sy tet Me dycz ny w Po zna niu, Polska Department of General Orthopedics, Musculoskeletal Oncology and Trauma Surgery, Poznań University of Medical Sciences, Poland STRESZCZENIEWstęp. Trzpień Zweymüllera jest dobrze znany i powszechnie stosowany w Europie od 1980 r. Nieliczni auto rzy wska zu ją na wy stę po wa nie za gęsz czeń ko ści gąb cza stej pod trzpie niem, na to miast do tąd nie opi sa no me cha ni zmu sto ją ce go u pod st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Decreases in BMD around the femoral implant after THA have been observed in a number of previous studies [20,21]. Particularly, in Zweymüller stems, bone absorption around the proximal area is due to stress shielding and cortical hypertrophy at the distal part [22,23]. In the current study, similar to previous reports, the amount of decrease of the BMD was shown in ROI 1 or 7.…”
supporting
confidence: 89%
“…Decreases in BMD around the femoral implant after THA have been observed in a number of previous studies [20,21]. Particularly, in Zweymüller stems, bone absorption around the proximal area is due to stress shielding and cortical hypertrophy at the distal part [22,23]. In the current study, similar to previous reports, the amount of decrease of the BMD was shown in ROI 1 or 7.…”
supporting
confidence: 89%
“…Bone tissue integration to implants requires a perfect initial and ultimate stability of their junction. This stability depends, to a great extent, on the shape and geometry of the implant, as well as on its surface coating, the preliminary fitting of the implant in the patient’s osseous bed, and on load distribution in the implant-bone junction [4,5]. Numerous reports have recently been published in the relevant literature, broadly covering the issues of understanding biofunctionality of different types of endoprostheses in the patient’s body, assessing, among other things, the long-term outcomes of alloplastics, bone tissue remodeling around the proximal and distal parts of prosthesis stem, comparing different types of endoprostheses (e.g., cemented or cementless ones, and short or long stems), assessing the causes of prosthesis loosening after implantation, and even evaluating the quality of life in patients who underwent alloplastic [6–9].…”
Section: Introductionmentioning
confidence: 99%